2014
DOI: 10.1371/journal.pone.0093624
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Texture Segmentation Framework for Segmentation of Capillary Non-Perfusion Regions in Fundus Fluorescein Angiograms

Abstract: Capillary non-perfusion (CNP) in the retina is a characteristic feature used in the management of a wide range of retinal diseases. There is no well-established computation tool for assessing the extent of CNP. We propose a novel texture segmentation framework to address this problem. This framework comprises three major steps: pre-processing, unsupervised total variation texture segmentation, and supervised segmentation. It employs a state-of-the-art multiphase total variation texture segmentation model which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…For example, Zheng et al. () proposed a new texture segmentation framework for the analysis of capillary non‐perfusion regions in FA which was satisfactory when compared to a reference standard of manual delineations. In contrast, OCT angiography automatically calculates the ischaemic areas in superficial and deep images.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zheng et al. () proposed a new texture segmentation framework for the analysis of capillary non‐perfusion regions in FA which was satisfactory when compared to a reference standard of manual delineations. In contrast, OCT angiography automatically calculates the ischaemic areas in superficial and deep images.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Construct the a±nity matrix A 2 R nÂn where its ith row and jth column element is de¯ned by Eq. (31).…”
Section: Exemplar-clustering Phasementioning
confidence: 99%
“…So the texture image segmentation aims at segmenting a textured image into several regions each of which has the same or similar texture feature, where texture is very important information in image processing since it presents the interest of most objects and often indicates contextual information of image pixels. 31 Because segmentation of texture images depends on pixel patterns that are di±cult to capture or de¯ne, the techniques using pixel patterns for texture images are more di±cult than the techniques of only using the intensity of pixels. There have been many di®erent approaches for segmentation, 3,12,[18][19][20]30,31 and some belong to supervised methods, while others belong to unsupervised methods.…”
Section: Introductionmentioning
confidence: 99%
“…Fundus fluorescein angiography (FA) is considered to be the gold standard for imaging patients with retinal pathologies . Few studies have shown automated segmentation of CNP regions in fundus fluorescein angiography (FFA) images .…”
Section: Introductionmentioning
confidence: 99%